High‐dose dexamethasone plus recombinant human thrombopoietin vs high‐dose dexamethasone alone as frontline treatment for newly diagnosed adult primary immune thrombocytopenia: A prospective, multicenter, randomized trial. Issue 12 (19th October 2020) - Yu, Yafei; Wang, Miaomiao; Hou, Yu; Qin, Ping; Zeng, Qingshu; Yu, Wenzheng; Guo, Xinhong; Wang, Jingxia; Wang, Xiaomin; Liu, Guoqiang; Chu, Xiaoxia; Yang, Lan; et al.
Abstract: We conducted a prospective, multicenter, randomized, controlled clinical trial to compare the efficacy and safety of high‐dose dexamethasone (HD‐DXM) plus recombinant human thrombopoietin (rhTPO), vs HD‐DXM alone in newly diagnosed adult immune thrombocytopenia (ITP) patients. Enrolled patients were randomly assigned to receive DXM plus rhTPO or DXM monotherapy. Another 4‐day course of DXM was repeated if response was not achieved by day 10 in both arms. One hundred patients in the HD‐DXM plus rhTPO arm and 96 patients in the HD‐DXM monotherapy arm were included in the full analysis set. So, HD‐DXM plus rhTPO resulted in a higher incidence of initial response (89.0% vs 66.7%, P < .001) and complete response (CR, 75.0% vs 42.7%, P < .001) compared with HD‐DXM monotherapy. Response rate at 6 months was also higher in the HD‐DXM plus rhTPO arm than that in the HD‐DXM monotherapy arm (51.0% vs 36.5%, P = .02; sustained CR: 46.0% vs 32.3%, P = .043). Throughout the follow‐up period, the overall duration of response was greater in the HD‐DXM plus rhTPO arm compared to the HD‐DXM monotherapy arm ( P = .04), as estimated by the Kaplan‐Meier analysis. The study drugs were generally well tolerated. In conclusion, the combination of HD‐DXM with rhTPO significantly improved the initial response and yielded favorable SR in newly diagnosed ITP patients, thus could be further validated as a frontline treatment for ITP. This study is registered as clinicaltrials.gov identifier: NCT01734044.